Market potentials for selected organic leafy vegetables (2015)
"Increased consumer awareness has raised concerns over food safety and production methods. In Nigeria, consumption of organic produce is low. This study assessed consumer willingness to pay for selected organic leafy vegetables. Data from 129 respondents were obtained using a simple random sampling technique. Conjoint analysis and contingent valuation were used to analyze willingness to pay and determinants of willingness to pay. Contingent valuation indicated that 84.5%, 76%, and 62.8% of the respondents were willing to pay extra for Amaranthus cruentus L., Celosia argentia L., and Cochorus olitorius L., respectively. Average willingness to pay a price premium was 46%, 42.4%, and 35.8% for A. cruentus, C. argentia, and C. olitorius, respectively. Conjoint analysis indicated that quality was the most valued attribute of leafy vegetables with relative importance of 42.2%. Income, health status, and work experience were key determinants of willingness to pay; all increasing the likelihood of willingness to pay. Income was significant with marginal effects of 0.005 and 0.006 for A. cruentus and C. olitorius, respectively. Health status was significant with marginal effects of 0.366 and 0.225 for A. cruentus and C. olitorius, respectively. Work experience was significant for all species. There is strong market potential for organic leafy vegetables, especially if quality is high and prices are reasonable. "